Fight for freedom and other writings on civil rights - Hughes, Langston, 1902-1967 (Hughes, Langston, 1902-1967. Works. 2001, 2001)
Nearing the end of a distinguished literary career that spanned nearly fifty years, Langston Hughes took on the daunting task of writing the official history of the national Association for the Advancement of Colored People (NAACP). Beginning with the social, political, and economic contexts that led to the founding of the NAACP in 1909 and ending with a summary of its targeted goals for 1963, Hughes attempted to write a history that would be comprehensive in scope and singular in its purpose of highlighting the ways in which the Association had a direct and positive influence on racial justice in the United States. Focusing on the individuals who had the greatest impact on the NAACP and the issues with which the organization was most concerned in its first fifty years of existence, Hughes produced the widely acclaimed Fight for Freedom, striking an exceptional balance between biography and cultural history. Long before the publication of Fight for Freedom, Hughes had begun writing nonfictional prose about these same issues as a regular columnist and essayist for the nation's most influential African American publications, including the Chicago Defender and Crisis. A selection of these popular columns and other essays - which reveal the extent to which Hughes's unique, varied, and sometimes Blues- tinged narrative voice shifted in tone over the course of his extensive career - is included in this volume. Hughes intersperses historical facts with compelling anecdotes that often frame subtly ironic commentaries on various themes. The result is history that provides a lens through which to view Hughes's attitudes in the early 1960s toward the ways the NAACP addressed the vital social, cultural, political, and economic issues central to its agenda. Fight for Freedom and Other Writings on Civil Rights makes a unique contribution to the oeuvre of an African American writer whose full significance to American literature, history, and culture will continue to be defined well into the twenty-first century.